Redescription of three basal anomodonts: a phylogenetic reassessment of the holotype of Eodicynodon oelofseni (NMQR 2913) - Duhamel, Alienor; Benoit, Julien; Wynd, Brenen; Wright, April Marie; Rubidge, Bruce (Frontiers in Earth Science, 2024)
The Dicynodontia (Therapsida: Anomodontia) is one of the most successful Permo-Triassic terrestrial tetrapod clades and the oldest specimens are recorded from the middle Permian Eodicynodon Assemblage Zone of South Africa. Their fossil record is abundant and species-rich across Pangea. By contrast, the fossil record of the basal-most anomodonts, which includes non-dicynodont anomodonts and early forms of dicynodonts, is patchy and their morphology and phylogeny are deduced from relatively few specimens. Discovered in 1982 and described in 1990, the holotype of Eodicynodon oelofseni (NMQR 2913) is one of the better-preserved early anomodont specimens. However, it has been suggested that E. oelofseni does not belong to the genus Eodicynodon. Here, using CT-scanning and 3D modeling, the skull of Eodicynodon oelofseni, Patranomodon nyaphulii and Eodicynodon oosthuizeni are redescribed.In the framework of this study, the application of 3D scanning technology to describe anatomical structures which were previously inaccessible in these fossils has enabled detailed redescription of the cranial morphology of the basal anomodonts Patranomodon, Eodicynodon oelofseni and Eodicynodon oosthuizeni and led to a greater understanding of their cranial morphology and phylogenetic relationships.Based on an anatomical comparison and phylogenetic analyses (Bayesian and cladistics) the phylogenetic relationships of basal anomodonts are reassessed and it is suggested that NMQR 2913 does not belong to the genus Eodicynodon but likely represents a separate genus basal to other dicynodonts. A new genus is erected for NMQR 2913. The study present in addition one of the first application of Bayesian Inference of phylogeny on Therapsida.